Implementation of Ex-Officio Policy on The Development of Batam Free Trade Zone and Free Port Area - Achmad, Amsakar; Syafri, Wirman; Achmad, Mansyur; Amalia, Rizki (Universitas Sultan Ageng Tirtayasa, 2024)
Governments implement policies to regulate societal frameworks and enhance state value, with one primary objective being the establishment of Batam as a Free Trade and Free Port Area to accelerate economic growth. This study examines the implementation of the ex-officio policy within Batam's free trade and free port area, highlighting the factors that either facilitate or hinder its execution. The initiative to designate Batam as a free trade zone originated in the 1970s, following the issuance of Presidential Decree No. 74 of 1971. However, over the past five decades, Batam's economic growth has been inconsistent, largely due to administrative conflicts between the Batam Industrial Development Authority (now the Batam Indonesia Free-Zone Authority) and the Batam Municipal Government. In response, the Indonesian government introduced Government Regulation No. 62 of 2019, appointing the Mayor of Batam as the ex-officio Chief Executive of the Batam Indonesia Free-Zone Authority to resolve these conflicts. While the policy aims to streamline governance and enhance development outcomes, its effectiveness remains contested, necessitating a comprehensive analysis of its implementation in the context of advancing Batam’s status as a Free Trade Zone and Free Port Area.